Efficient Compound Barge Design - Glib Ivanov (International Journal of Marine Engineering Innovation and Research, 2021)
During the twentieth century, naval architects worked to improve the performance of pusher tugs. The ropes used to secure the pusher to a barge were prone to tearing; this problem was remedied by the development of several coupling devices, including one that was highly advanced. Previous researchers have identified three major issues regarding this matter: the vessel's seaworthiness when not coupled, safety, and suboptimal structure. The purpose of this paper is to propose solutions to the aforementioned problems by introducing an efficient compound vessel design. Comparative advantages of compound vessels are analysed. Designs of a compound barge and effective coupling mechanism are introduced. Prospective weight reduction and economic advantages of coupled barges are calculated and analysed.